NEW SPECIES OF LATE EOCENE FEATHER-WINGED BEETLES (COLEOPTERA, PTILIIDAE) FROM THE ROVNO AND BALTIC AMBER - Polilov A.A.; Perkovsky E.E. (My University, 2004)
Fossil beetles of the family Ptiliidae are reviewed. Two new species, Micridium groehni sp. nov. and Ptinella rovnoensis sp. nov., are described from the Baltic and Rovno amber.
Keywords: Eocene; Cenozoic::Paleogene::Eocene; Кайнозой::Палеоген::Эоцен